2008
DOI: 10.1111/j.1365-2125.2008.03251.x
|View full text |Cite
|
Sign up to set email alerts
|

A limited sampling strategy for tacrolimus in renal transplant patients

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Tacrolimus trough concentration is being currently used for dose individualization.• Limited sampling strategies (LSS) have been developed and validated for renal transplant patients.• Earlier literature has suggested that measurement of tacrolimus AUC is more reliable than trough with respect to both rejection and nephrotoxicity. WHAT THIS STUDY ADDS• Four thousand renal transplants take place annually in India, with many patients prescribed tacrolimus in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…92 Thus, AUC-guided tacrolimus TDM has been proposed with a target of 150 to 200 h*ng/mL. Numerous LSS-based on regression linear method [103][104][105][106][107] and Bayesian estimator 108 have been developed but only in adults and no further validation was conducted in children. Therefore, validation of pediatric-specific LSS for tacrolimus should be performed in future investigations.…”
Section: How To Monitor Tacrolimus In Children: Is It Different From mentioning
confidence: 99%
“…92 Thus, AUC-guided tacrolimus TDM has been proposed with a target of 150 to 200 h*ng/mL. Numerous LSS-based on regression linear method [103][104][105][106][107] and Bayesian estimator 108 have been developed but only in adults and no further validation was conducted in children. Therefore, validation of pediatric-specific LSS for tacrolimus should be performed in future investigations.…”
Section: How To Monitor Tacrolimus In Children: Is It Different From mentioning
confidence: 99%
“…The correlation coefficients were between 0.95 and 0.99 and %RMSE between 4.1 and 8.6. Mathew et al 21 have found that the C/C 1.5 combination was highly correlated with the tacrolimus AUC (r 2 = 0.95). According to our results, the inclusion of a third point in the LSS seems to be superfluous because the differences in correlation coefficients and prediction error indicators between 2-and 3-time point LSS are very slight.…”
Section: Discussionmentioning
confidence: 95%
“…8,17,21 However, this time point becomes less predictive for AUC after 1 year of exposure to tacrolimus, and thus it could not be considered as a reliable parameter for the TDM of this drug.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, TAC was examined to show which blood sampling point is the best correlated with AUC as CYA. One study reported that C o is the best correlated with AUC 27) , whereas another study suggested that a formula with fewer blood sampling points, and not C o , is the most closely correlated with AUC (limited sampling strategy) [28][29][30][31] .…”
Section: Tacrolimusmentioning
confidence: 99%